Pengaruh pemberian tepung singkong (Manihot utilissima Pohl.) terhadap performa Burung Puyuh jantan (Coturnix coturnix japonica) - Lisnawaty Silitonga; Robertho Imanuel; Rini Sulistia N (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
This research studied to know the effect of feed cassava flour (Manihot utilissima Pohl.). This research was designed by Completely Randomized Design (CRD) and Variant Analysis (ANOVA), if the obtained data showed significant differences then tested further using HSD test α = 5%. Four (4) treatment that P0 (feed control treatment), P1 (feed treatment 95% + 5% cassava flour), P2 (feed treatment 90% + 10% cassava flour) and P3 (feed treatment 85% + 15% cassava flour) and five replication each replication consists 4 quail. The result showed not significant (P>0.05) on all treatments, but the substitution 5% of cassava flours still consumed by quail without rising negative effects. Key words : Cassava flour, feed, performance, quail males.